Selective leaching of Al from hypereutectic Al-Si alloy to produce nano-porous silicon (NPS) anodes for lithium ion batteries. (10th September 2019) - Pathak, Anil D.; Chanda, Uttam K.; Samanta, Kousik; Mandal, Animesh; Sahu, Kisor K.; Pati, Soobhankar
Abstract: Silicon is expected to play a major role in the development of the next generation lithium-ion batteries. However, high volume expansion (∼300%) and kinetic sluggishness make it a commercially unviable standalone anode material. To mitigate these issues, we present a novel approach of making nano-porous silicon from readily-available hypereutectic aluminum-silicon alloy through an industrially scalable de-alloying process. We provide key insights into this novel process through the first principle calculations, taking into account various thermodynamic and kinetic effects. Under identical test conditions, commercial silicon sustains only 40 cycles, while nano-porous silicon has no issues until the test terminates at 300 cycles. We also present a strong case for the economic viability of the lithium-ion batteries with nano-porous silicon anode in the automobiles industry based on cost-savings in various front and enhancements in key performance metrics. Graphical abstract: Image 1 Highlights: Nano-porous silicon (NPS) developed using de-alloying of hyper eutectic Al-Si alloy. Thermodynamic and kinetic of the process evaluated by the first principle calculations. NPS anode retained a capacity of ∼1000 mAh g −1 after 300 cycles. One order of magnitude cost reduction can be achieved for the NPS anode material.